Examination of a practical method for copper enrichment of euryhaline rotifers (Brachionus plicatilis) as diet of Eriocheir sinensis zoea larvae. (14th February 2013) - Sun, S.; Chen, L.; Ge, X.; Qin, J.
Abstract: In this study, an effective method to enrich the rotifer Brachionus plicatilis with copper was developed as a feed for the Chinese mitten crab Eriocheir sinensis zoea larvae. Changes in the concentrations of other minerals in rotifers were also examined when copper was added for rotifer enrichment. The ability of Chlorella to absorb waterborne copper is much higher than that of rotifers, and hence, copper was preaccumulated in Chlorella before its ingestion by rotifers. The copper content in rotifers was comparable to the dietary copper requirement of the crab larvae when the rotifers were enriched with 0.1 mg Cu g −1 Chlorella for 12 h. Further enrichment in rotifers with Cu‐enriched Chlorella and lipid emulsions did not significantly change the profile of major fatty acids and mineral composition in the rotifers. Evidence shows the feasibility of copper enrichment in rotifers using microalgae that can accumulate copper. This study indicates that copper in rotifers can be enriched by feeding copper‐enriched algae at a concentration of 0.1–0.2 mg Cu g −1 Chlorella . The developmental rates of E. sinensis can be improved by feeding zoea larvae with copper‐enriched rotifers, but survival rates were not affected by dietary copper enrichment.